A Systematic Literature Review of Assessment Tools for Programming Assignments - Souza, Draylson M.; Felizardo, Katia R.; Barbosa, Ellen F. (Proceedings / Conference on Software Engineering Education & Training, 2016)
The benefits of using assessment tools for programming assignments have been widely discussed in computing education. However, as both researchers and instructors are unaware of the characteristics of existing tools, they are either not used or are reimplemented. This paper presents the results of a study conducted to collect and evaluate evidence about tools that assist in the assessment of programming assignments. To achieve our goal, we performed a systematic literature review since it provides an objective procedure for identifying the quantity of existing research related to a research question. The results identified subjects in the development of new assessment tools that researchers could better investigate and characteristics of assessment tools that could help instructors make selections for their programming courses.